Pengaruh Media Pembelajaran Kotak Pintar Baca (Smart Box) Terhadap Kemampuan Membaca Siswa Kelas II pada Mata Pelajaran Bahasa Indonesia di SDS Muhammadiyah 18 Medan - Rizka Nabillah; Sahkholid Nasution; Muhammad Syaifullah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of the Smart Box learning media on the reading ability of class II students in the Indonesian Language subject at SDS Muhammadiyah 18 Medan. This study is a quantitative study with a quasiexperimental research method with a quasi-experiment type. The sample of this study was taken using the Random Sampling technique or simple random sampling consisting of two classes, namely class II-A totaling 26 students as an experimental class using the Smart Box media and class II-C totaling 26 students as a control class without using the Smart Box media. The data collection technique used in this study was a performance test (reading test) using Pretest and Posttest. The results of the study from both classes, namely in the pretest, had an average (mean) of the experimental class of 55.73 and the control class of 45.38. In the posttest, the average (mean) value of the experimental class was 87.31 and the control class was 61.73. The results of the hypothesis showed a t-count value of 12.767> t-table 1.675, which means that Ho is rejected and Ha is accepted. Thus, the hypothesis states that the smart reading box media (Smart box) has an effect on students' reading ability in the Indonesian language subject for class II at SDS Muhammadiyah 18 Medan.